Public Opinion on Poland’s Aid for Less Developed Countries and Ukraine - Jasiecki, Krzysztof (Studia z Polityki Publicznej, 2024)
After membership in the EU development aid became one of the new areas of Polish public policy. The article interprets the evolution of public opinion in the selected issues of Polish development assistance with the use of a secondary analysis of surveys conducted at the request of MFA by Kantar Public. It proves that knowledge about this issue has a niche range in Polish society, is rarely present in media, and few Poles declare any involvement in helping less developed countries. It presents the motivations of supporters and opponents of development aid, their social profiles, changes in the perception of aid, preferences for the geographical location, the public perception of supporting Ukraine.